Spectral response analysis of selected Philippine agricultural soils in varying nutrient conditions - Manguerra, Juliet Regori
Three major soil orders commonly used for agricultural purposes in the Philippines are Alfisols, Inceptisols and Ultisols. Representative sample were collected for these soil orders composed of dry and wet and with the introduction of increasing levels of elemental nutrient such as nitrogen (N), phosphorus (P), and potassium (K). The measurement of spectral reflectance was carried out in the laboratory using a spectrometer at a wavelength interval of 400 to 850 nanometers. Mean spectral reflectance values were computed and plotted as spectral curves for each soil order and at varying levels of N, P and K. The spectral responses of each soil order and the spectral behavior of the elemental nutrients were analyzed using analysis of variance (ANOVA); spectral derivative analysis; and spectral resampling technique to sensors of selected satellite images. ANOVA was used to determine whether the soil orders and the different nutrients levels differ significantly in reflectance responses. Derivative analysis established the most responsive wavelength and the degree of differences in reflectance values among the samples. Spectral resampling matched the measured spectral data using the spectral sensitivities or filter windows of the sensors of Landsat Thematic Mapper/Multi Spectral Scanner (Landsat TM/MSS), Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER)and System Pour l'observation de la Terre (SPOT) along the electromagnetic spectrum. The central wavelength absorption by soil order and nutrient conditions was derived for the respective bands of the satellite sensors. Spectral curve were plotted to the corresponding bands of Landsat TM/MSS, ASTER and SPOT. The analysis of variance proved that there is a significant difference of the mean reflectance values of soil order and moisture content. Correspondingly, the increasing levels of N, P and K by soil order demonstrated significant differences in the mean reflectance values. Spectral derivative analysis confirmed that Alfisols, Inceptisols and Ultisols are distinguishable in wavelength ranges 0.45-0.52 µm, 0.52-0.60 µm, and 0.63-0.69 µm of the electromagnetic spectrum. Spectral response of phosphorous among the soil orders is distinct in the 0.76-0.85 µm, 0.45-0.52 µm, and 0.52-0.60 µm for Alfisols, Inceptisols and Ultisols, respectively. The analysis of spectral responses of the soil orders and elemental nutrients examined, in relation to other soil attributes opens up possibilities for development of spectral libraries which can support image analysis particularly for soil related stu